Virtual reality for pediatric periprocedural care. Issue 3 (June 2021) - Wang, Ellen; Thomas, James J.; Rodriguez, Samuel T.; Kennedy, Kristin M.; Caruso, Thomas J.
Abstract : Purpose of review: Commercial availability of virtual reality headsets and software has exponentially grown over the last decade as it has become more sophisticated, less expensive, and portable. Although primarily used by the general public for entertainment, virtual reality has been adopted by periprocedural clinicians to improve patient experiences and treatments. The purpose of this review is to explore recently reported evidence for virtual reality effectiveness for pediatric periprocedural care and discuss considerations for clinical implementation. Recent findings: In the preprocedure setting, practitioners use virtual reality to introduce children to periprocedural environments, distract attention from preprocedural vascular access, and increase cooperation with anesthesia induction. Intraprocedure, virtual reality decreases sedation requirements, and in some instances, eliminates anesthesia for minor procedures. Virtual reality also augments pain reduction therapies in the acute and extended rehabilitation periods, resulting in faster recovery and improved outcomes. Virtual reality seems to be well treated for pediatric use, given close clinical care and carefully curated content. Summary: Given the multiple clinical applications of virtual reality to supplement pediatric periprocedural care, practitioners should consider developing clinical programs that reliably provide access to virtual reality. Future research should focus on identification of patient characteristics and types of software that yield optimal patient outcomes.